Prosperity for All / Ending Extreme Poverty : A Note for the World Bank Group Spring Meetings 2014 - World Bank (Washington, DC, 2014)
In 2013, the Board of Governors endorsed two new goals for the World Bank Group (WBG). First, the WBG would commit its full energies to bringing an effective end to extreme poverty by 2030. This means reducing to no more than 3 percent the fraction of the world’s population living on less than $1.25 per day. Second, the WBG would focus on ensuring that the benefits of prosperity are shared by shifting from a focus on average economic growth to promoting income growth amongst the bottom 40 percent of people. Critically, the goals need to be achieved in a sustainable manner, thus helping secure the long-term future of the planet and its resources, ensuring social inclusion, and limiting the economic burdens of future generations. This short note begins by looking at progress to date in reducing global poverty and discusses some of the challenges of reaching the interim target of reducing global poverty to 9 percent by 2020, which was set by the WBG President at the 2013 Annual Meetings. It also reports on the goal of promoting shared prosperity, with a particular focus on describing various characteristics of the bottom 40 percent. A more detailed report with policy recommendations in the areas of ending extreme poverty and boosting shared prosperity is due for release at the Annual Meetings later this year.